From active duty to activism: how moral injury and combat trauma drive political activism and societal reintegration among Israeli veterans - Levy, Adi; Gross, Michael L. (Frontiers in Public Health, 2024)
Trigger warning This article deals with combat experiences and their consequences and could be potentially disturbing. Introduction Moral injury (MI) is a severe form of combat trauma that shatters soldiers’ moral bearings as the result of killing in war. Among the myriad ways that moral injury affects veterans’ reintegration into civilian life, its impact on political and societal reintegration remains largely unstudied but crucial for personal, community, and national health. Methods 13 in-depth interviews examine combat soldiers’ exposure to potentially morally injurious events (PMIEs) that include killing enemy combatants, harming civilians, and betrayal by commanders, the military system, and society. Interviewees also described their political activities (e.g., voting, fundraising, advocacy, protest) and social activism (e.g., volunteering, teaching, charitable work). Interviewees also completed the Moral Injury Symptom Scale. Results Two distinct narratives process PMIEs. In a humanitarian narrative, soldiers hold themselves or their in-group morally responsible for perpetrating, witnessing, or failing to prevent a morally transgressive act such as killing or injuring civilians or placing others at unnecessary risk. In contrast, a national security perspective blames an out-group for leaving soldiers with no choice but to act in ways that trigger moral distress. Associated with shame and guilt, the humanitarian perspective triggered amends-making and social activism after discharge. In contrast, a national security perspective associated with anger and frustration fostered protest and intense political activism. Discussion Despite its harmful health effects, moral trauma and injury can drive intense political and social activism, depending upon the narrative veterans adopt to interpret PMIEs. Aside from moral injury’s personal, familial, and social effects, moral injury drives veterans’ return to the political arena of civil society. As such, veterans play a central role in politics and dramatically affect post-war policy in democratic nations following conflict.